The Counsellor, the Agency, and Organization Development - McBryde, Ron (Canadian Journal of Counselling and Psychotherapy, 2011)
Counselling process and skills can be adapted to Organization development (OD) and some counsellors may act as organization change agents. However counselling skills in and of themselves are not sufficient in undertaking comprehensive OD interventions. In fact bringing about change in a large and complicated counselling agency or mental health centre is a complex intervention requiring additional skills and knowledge on the part of both the counsellor and the industrial-oriented OD specialist. This paper proposes theory and practice changes for applying Organization development to counselling and other human service organizations.